The Healthy Steps Study: A randomized controlled trial of a pedometer-based Green Prescription for older adults. Trial protocol - Schluter Philip J; Garrett Nicholas; Kerse Ngaire; Schofield Grant M; Kolt Gregory S; Ashton Toni; Patel Asmita (BMC, 2009)
Abstract Background Graded health benefits of physical activity have been demonstrated for the reduction of coronary heart disease, some cancers, and type-2 diabetes, and for injury reduction and improvements in mental health. Older adults are particularly at risk of physical inactivity, and would greatly benefit from successful targeted physical activity interventions. Methods/Design The Healthy Steps study is a 12-month randomized controlled trial comparing the efficacy of a pedometer-based Green Prescription with the conventional time-based Green Prescription in increasing and maintaining physical activity levels in low-active adults over 65 years of age. The Green Prescription interventions involve a primary care physical activity prescription with 3 follow-up telephone counselling sessions delivered by trained physical activity counsellors over 3 months. Those in the pedometer group received a pedometer and counselling based around increasing steps that can be monitored on the pedometer, while those in the standard Green Prescription group received counselling using time-based goals. Baseline, 3 month (end of intervention), and 12 month measures were assessed in face-to-face home visits with outcomes measures being physical activity (Auckland Heart Study Physical Activity Questionnaire), quality of life (SF-36 and EQ-5D), depressive symptoms (Geriatric Depression Scale), blood pressure, weight status, functional status (gait speed, chair stands, and tandem balance test) and falls and adverse events (self-report). Utilisation of health services was assessed for the economic evaluation carried out alongside this trial. As well, a process evaluation of the interventions and an examination of barriers and motives for physical activity in the sample were conducted. The perceptions of primary care physicians in relation to delivering physical activity counselling were also assessed. Discussion The findings from the Healthy Steps trial are due in late 2009. If successful in improving physical activity in older adults, the pedometer-based Green Prescription could assist in reducing utilisation of health services and improve cardiovascular health and reduction of risk for a range of non-communicable lifestyles diseases. Trial registration Australian and New Zealand Clinical Trials Registry ACTRN012606000023550